The Justification Clause of Philippians 3.12 Past and Current Appraisals of a Striking Variant Reading - Giffin, Ryan Kristopher (2021)
A minority of witnesses to the text of Phil. 3.12 (e.g., P46, GA 06, 010, 012, Irenaeus [Latin Translation], Ambrosiaster) attest to a reading in which Paul claims he has not yet been justified (or made/found righteous [δικαιόω]). Scholars have labeled the reading ‘intriguing’, ‘very interesting’, ‘striking’, and ‘astounding’. Yet, in spite of such lofty descriptors, little extensive attention has been devoted to this textual issue. All but a handful of scholars who have addressed the reading have denied it a place in the initial text. However, its attestation in P46, the high potential for parablepsis, the difficulty of explaining the reading as a later insertion, and its coherence with Pauline references to final justification at the last judgment have resulted in reassessments of the issue in more recent scholarship. This article provides an overview of past and current scholarly appraisals of the reading and offers some suggestions for future research.
Keywords: Righteousness; Variant Reading; Textual Criticism; Text; Philippians; justified; Justification; Apostle Paul